Synthesis of 5-Fluorouracil (5-FU) coated platinum nanoparticles and apoptotic effects on U87 human glioblastoma cells - Atena Abed; Merat Karimi; Majid Nejati; Michael R. Hamblin; Seyed Abbas Mirzaei; Mostafa Sarvizadeh; Hamed Mirzaei (Cancer Cell International)
Abstract Background 5-Fluorouracil (5-FU) is a widely used chemotherapeutic agent; however, its clinical application is often limited by systemic toxicity and the development of drug resistance. To enhance its therapeutic efficacy, novel drug delivery strategies are under investigation. This study evaluated the use of platinum nanoparticles (PtNPs) as a nanocarrier system for 5-FU delivery to glioblastoma cells, focusing on their effects on apoptosis-related proteins. Methods The binding affinity and interactions of 5-FU with key apoptotic proteins (BAX, Bcl2, and Caspase-3) were assessed using molecular docking and validated through molecular dynamics (MD) simulations. PtNPs were synthesized and characterized via scanning electron microscopy (SEM), X-ray diffraction (XRD), and dynamic light scattering (DLS). Drug loading and encapsulation efficiency were determined, and cytotoxicity assays were conducted in U87 glioblastoma cells. The expression levels of apoptosis-related genes and proteins were evaluated to determine the biological impact of the formulations. Results Docking results confirmed effective binding of 5-FU to Bcl2, Caspase-3, and BAX, with MD simulations supporting stable complex formation, particularly with Bcl2 and Caspase-3. The synthesized PtNPs exhibited favorable physicochemical properties, including uniform morphology and high drug loading efficiency. In vitro release studies revealed a sustained release profile for the PtNPs/5-FU formulation. Furthermore, PtNPs/5-FU significantly downregulated the expression of EMT- and proliferation-related genes (cyclin D1, ZEB1, and Twist) and suppressed Bcl2 protein levels, resulting in enhanced apoptosis in U87 cells. Conclusion PtNPs effectively functioned as a delivery platform for 5-FU, improving its release kinetics and promoting apoptotic responses while potentially minimizing systemic toxicity. These findings support further exploration of PtNP-based drug delivery systems as a promising strategy for glioblastoma treatment.